PENGARUH MEREK DAN CITRA DIRI TERHADAP KEPUASAN KONSUMEN PRODUK TELEPON SELULER DI KOTAMADYA YOGYAKARTA - Wendri Rusli (Fakultas Bisnis Universitas Kristen Duta Wacana, 2011)
ABSTRACT Thisstudy aims to analyze the effect of brand preference and self image congruency on customers satisfaction using seluler's telephonic product. This study uses survey methods. Survey’s region is at Yogyakarta city.The sampels used in this study are 100 respondents. This research uses multiple regression as its data analyses. The results show that self image congruency and brand preference influenceon customers satisfaction using seluler's telephonical product. Also, this study indicates that self image congruency’s role is more dominanton customer satisfaction. Keywords: self image congruency, brand preference, and consumer satisfaction